Pengaruh Gaya Kepemimpinan Terhadap Motivasi Kerja Karyawan Pada PT. Matahari Departement Store di MegaMall, Manado - Wowor, Wulan Qimberly; Sumayku, Sontje M.; Sambul, Sofia A. P. (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
This study aims to determine the Effect of Leadership Style on Employee Motivation at PT. Matahari Department Store at Mega Mall Manado. The research method used in this research is quantitative associative and data collection carried out by survey. The population in this research is all employees who work at Matahari Mega Mall. The sample determined in this study was using Slovin formula as many as 44 respondents using Correlation Analysis, t Test, and Simple Linear Regression. The results of R show 0.370 means that the relationship between Work Leadership and Motivation Style is Quite Strong, R Square shows 0, 137 which means Work Motivation Variables are influenced by 13, 70% by Leadership Style Variables and the remaining 86.30% are influenced by other variables not used in this study. The t test shows a significant value of 0.013, which means that the Leadership Style Variable has a Positive and Significant effect on the Employee Motivation Variables. The Simple Linear Regression equation obtained is Y = 25,521 + 0,607.X1. From these equations, the Constants show that if the Leadership Style is worth Zero, then Work Motivation is equal to 25,521. The Coefficient of Leadership Style is 0.607, meaning that if the other variables are fixed and the Leadership Style increases by 1 point or 1%, Work Motivation will increase by 0.607 per one point / unit. From the results above it can be concluded that the leadership style has a positive influence on Employee Work Motivation, it is expected that the company maintains and improves the factors that influence Employee Work Motivation.